Efficacy of radical reactions of isocyanides with heteroatom radicals in organic synthesis - Ogawa, Akiya; Yamamoto, Yuki (Beilstein Journal of Organic Chemistry, 2024)
Isocyanide is a promising synthetic reagent not only as a one-carbon homologation reagent but also as a nitrogen source for nitrogen-containing molecules. Because of their isoelectronic structure with carbon monoxide, isocyanides also react with nucleophiles, electrophiles, carbon radicals, and transition metal reagents, and are widely used in organic synthesis. On the other hand, the use of isocyanides in reactions with heteroatom radicals is limited. However, the reaction of isocyanides with heteroatom radicals is a promising synthetic tool for the construction of nitrogen-containing organic molecules modified with a variety of heteroatoms. In this Perspective, we review the addition and cyclization reactions of heteroatom radicals with isocyanides and discuss the synthetic prospects of the reaction of isocyanides with heteroatom radicals.
Keywords: aza-Bergman cyclization; heteroatom-mixed system; imidoyl radical; isocyanide; radical addition; radical cyclization